LANDSCAPE ECOLOGICAL PATTERN OF TROPICAL AGRO-FORESTRY EFFORTS AT EDUCATIONAL FOREST LANDSCAPE OF MOUNT WALAT, SUKABUMI - Wahyu Hidayat, Imawan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 5 No 1, 2012)
The process of urbanization has changed the face of the landscape, not only in urban environments, but it also has expanded the areas around it. The changes in land use are increasing not only occurs in areas formerly categorized a semi-intensive, such as agricultural lands, but also in extensive and protection areas. However, in some periphery still characterizes the function of a good environment; especially in rural areas the changes that occurred were limited to their own needs (subsistence), as in Mount Walat, Sukabumi. This study aims to identify and analyze the tropical agro-forestry efforts and to provide landscape ecological pattern in order to preserve the environment and social culture. The method used in this study was a site survey method with focusing on the biophysical condition of the site and analysis of reports or other sources regarding the management processes undertaken. Mount Walat ± 359 Ha area of forest is guided by land use pattern that is divided into four characters, i.e., forest ecosystem, opened forest, ownership land, and countrified. Its area of ± 70 Ha was managed as agro-forestry land. The form of tropical agro-forestry in the country side around the site consists of yard and mixture garden, while in the arable land is a mixture garden. In order to prevent of destruction, then the manager invites Hegarmanah villagers to cooperate in maintaining its sustainability by allowing land to cultivated in Mount Walat agro-forestry, with the terms agreed by both parties, without damaging the forest ecosystem. The study was suggested that the community structures and developmental pathways which arised across a gradient of disturbance frequencies can provide models for alternative agro-forestry solutions. Addressing multiple objectives and sustainability in a complex biophysical and socioeconomic system ought to be a challenging and exciting enterprises.
Keywords: Change, land use, tropical agro-forestry, landscape ecology, pattern, sustainability.